ABAB‐Symmetric Tetraalkyl Titanyl Phthalocyanines for Solution Processed Organic Field‐Effect Transistors with Mobility Approaching 1 cm2 V−1 s−1. (20th December 2012) - Dong, Shaoqiang; Bao, Cheng; Tian, Hongkun; Yan, Donghang; Geng, Yanhou; Wang, Fosong
<x xml:space="preserve">Abstract</x> In crystals, tetraalkyl vanadyl phthalocyanines (OVPc‐Cn) and tetraalkyl titanyl phthalocyanines (OTiPc‐Cn) with ABAB symmetry adopt a 2D slipped π–π stacking motif with alkyl chains locating in the space between semiconducting layers formed by Pc cores. Hole mobility approaching 1 cm2 V−1 s−1 is achieved for spin cast OFETs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>